A Case Report on Chronic Kidney Disease (CKD) through LLHWI Therapy and the DIP Diet (A Plant-Based Anti-Inflammatory Dietary Plan) - Biswaroop Roy Chowdhury (AYUSHDHARA, 2025)
Chronic Kidney Disease (CKD) is a progressive condition affecting 10-15% of the global population, often linked to diabetes, hypertension, and obesity. Its advanced stages, marked by reduced glomerular filtration rate (GFR) and elevated serum creatinine levels, typically require invasive treatments like dialysis or transplantation, posing significant burdens. This case study highlights patient, a 52-year-old CKD patient whose condition worsened despite conventional treatments. By August 2024, her creatinine level reached 9.1mg/dL, prompting recommendations for dialysis. Seeking alternatives, she adopted LLHWI Therapy and the DIP Diet at HIIMS Hospital. Within three days, her creatinine dropped to 7.4mg/dL, symptoms resolved, and she discontinued all medications. Over 20 days, her creatinine further declined to 6.4mg/dL, remaining symptom-free. This case demonstrates the potential of holistic and dietary interventions in managing CKD, emphasizing the need for further research to validate and integrate these therapies into conventional care for optimal outcomes.